Editorial - International Journal of Sustainable Energy Planning and Management Volume 23 - Johannsen, Rasmus Magni; Østergaard, Poul Alberg (International Journal of Sustainable Energy Planning and Management, 2019)
This editorial introduces the 23rd volume of the International Journal of Sustainable Energy Planning and Management. This volume presents research on the robustness of energy modelling, firstly through an assessment of the accuracy of heat demand estimations compared to measured data, followed by an examination of assessment of the robustness of energy modelling relative to the results’ dependency on input time series. Subsequently, challenges to the integration of renewable energy are reviewed, followed by a case from Iran investigating a 100% renewable energy system for desalination. Finally, the issues of technology prioritization for energy efficiency purposes and the development of energy indicators are tackled.